Giant haemorrhagic hepatic cyst with flame-like morphology in a patient with polycystic kidney and liver disease. (August 2021) - Brusic, Ana; Oo, June; Stella, Damien L; Simkin, Paul M; Loveday, Benjamin PT
Introduction: Intracystic haemorrhage is a rare complication of hepatic cysts, and is often mistaken for a malignant lesion. Case Report: A 55-year-old female with a history of polycystic kidney and liver disease presented with a six-month history of abdominal distension, abdominal pain, early satiety, shortness of breath and 5 kg of weight loss. Imaging revealed a 20 cm mixed solid-cystic hepatic lesion containing peripheral avascular mobile echogenic material with a flame-like morphology. After experiencing symptomatic relief from ultrasound-guided aspiration, the patient underwent cyst fenestration for more definitive treatment. Discussion: Haemorrhagic hepatic cysts are uncommon and may present on imaging as having lace-like retractile clot, internal layering or shading of separating blood products or avascular mobile flame-like excrescences. The presence of avascular mobile flame-like excrescences appears to be a unique feature of haemorrhagic hepatic cysts. Conclusion: While haemorrhagic hepatic cysts are rare and commonly mistaken for biliary cystadenomas or adenocarcinomas, the identification of particular features on high-resolution magnetic resonance imaging and contrast-enhanced ultrasound can lead to the correct diagnosis.